PELATIHAN PEMBUATAN NUGGET IKAN LELE UNTUK PENANGGULANGAN STUNTING KEPADA ORGANISASI PROFESI BIDANG PENDIDIKAN DAN MASYARAKAT KADER DI KOTA TASIKMALAYA - Marwan, Iis; Wahidah, Ida; Rahmat, Agus Arief (LPPM Univeristas Siliwangi, 2025)
The large number of processed fish on the market does not necessarily guarantee that the processed fish has a level of cleanliness and nutritional content that is good for health. One form of processed food that children like is nuggets. By processing it into nuggets, fish becomes easy to eat, making it suitable for use as food for children. The objectives of this activity are (1) Training educational organization administrators and community partners in making processed catfish nuggets; (2) Providing catfish nuggets to people who have stunted children; (3) introduce various fish preparations that are healthy, nutritious, delicious and definitely liked by children, (4) teach how to prepare food made from fish. This activity was carried out in Kahuripan Village, Tawan District, Tasikmalaya City, assisted by KKN group 41 students from Siliwangi University. Activities are carried out through counseling and training with several stages, namely lectures, direct demonstration and practice, providing leaflets, and monitoring. Achievement of activities in the form of education on making catfish nuggets and their handling by partners. The number of participants was 80 cadres. The conclusion of this activity is that by increasing the ability of cadre administrators in making catfish nuggets, the outreach program has been successful in increasing mothers' insight into making a variety of fish-based foods, as well as providing food for stunted children.